Permohonan PKPPU Oleh Nasabah PT. Asuransi Jiwa Kresna: Analisis Terhadap Putusan Nomor 389/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst) - Widjaja, Clement Nathan (Fakultas Hukum Universitas Trisakti, 2022)
In the insurance business often happens one party has failed to pay which can end up being applied for Pailit or “Delayed Debt Payment Obligation (PKPU)” as it happens in “PT. Asuransi Jiwa Kresna was applied for by the CPP by one of his countrymen. Is the application procedure of the CPPU carried out by the customer of PT. Asuransi Jiwa Kresna has been in accordance with the provisions of the laws in the field of insurance and whether the judgment No. 389/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst concerning the CPPU P.T. Asuransi Jiwa Kresna by the consumer “has been in conformity with the regulations of the legislation in” insurance, is the subject of the issue being discussed.”The research method used is a normative method of research that is descriptive based on secondary data, which is qualitatively analyzed with deductive conclusions. The results of the study describe that the “procedure of application for delayed payment of debt obligations by the client of PT. Asuransi Jiwa Kresna to the Court of Appeal is not in accordance with the provisions of Article 50 paragraph (1) of the Act No.40 of 2014 on Insurance Jo Article 223 of the KPKPU Act states that “the only person who can file an application of PKPU against an insurance company is the Financial Services Authority and the Decision No. 389/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst does not comply with the Law No. 40 of 2014 concerning Insurance, because it accepts the request of the customer, which the application should be made by the Financial Service Authority.